PENGEMBANGAN LITERASI DAN NUMERASI MELALUI KAMPUS MENGAJAR ANGKATAN 2 SD INPRES PAGA - Jessi Claudia Boe (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Abstract: Teaching Campus Batch 2 is one of Merdeka Campus' policies on the type of teaching activities in schools. This program invites students to contribute directly to the education of elementary and junior high school students in schools throughout Indonesia, especially in the 3 T areas (lagging, outermost, and leading). The Teaching Campus Program Batch 2, especially at the Paga Inpres Elementary School, has been going on for 5 months, from August to December 2021. The activities carried out are Knowledge Transfer, Technology Transfer and Administrative Affairs. The purpose of this research is to see the development of literacy and numeracy for elementary school students in Paga's Presidential Instruction, where there are various obstacles and challenges for us campus students teaching and for students in the process of improving literacy and numeracy development. The method used in this study is the method of habituation in the sense that students can develop literacy and numeracy in the elementary school. The final result in this study is that students can develop literacy and numeracy with activities that Campus Teaching students have done at Paga Inpres Elementary School.Keywords: Campus Teaching, Literacy, and Numeration Abstrak: Kampus Mengajar Angkatan 2 adalah salah satu kebijakan Kampus Merdeka pada jenis kegiatan Mengajar di sekolah. Program ini mengajak mahasiswa untuk berkontribusi langsung bagi pendidikan peserta didik SD dan SMP pada sekolah-sekolah di seluruh Indonesia khususnya di daerah 3 T ( tertinggal,terluar, dan terdepan). Program Kampus Mengajar Angkatan 2 ini khususnya di sekolah dasar inpres Paga sudah berlangsung selama 5 bulan yaitu dari bulan Agustus- Desember 2021. Adapun kegiatan-kegiatan yang dilakukan yaitu Transfer Ilmu Pengetahuan, Transfer Teknologi dan Urusan Administrasi, Tujuan dari penelitian ini adalah untuk melihat pengembangan literasi dan numerasi peserta didik sekolah dasar inpres Paga yang dimana terdapat berbagai hambatan dan tantangan tersendiri bagi kami mahasiswa kampus mengajar dan bagi peserta didik dalam proses meningkatkan pengembangan literasi dan numerasi. Metode yang digunakan dalam penelitian ini yaitu metode pembiasaan dalam arti peserta didik dapat mengembangkan literasi dan numerasi di SD tersebut. Hasil akhir dalam penelitian ini adalah peserta didik dapat mengembangkan literasi dan numerasi dengan kegiatan-kegiatan yang telah mahasiswa Kampus Mengajar lakukan di Sekolah Dasar Inpres Paga.Kata kunci: Kampus Mengajar, Literasi, dan Numerasi